Clinical, Immunological and Molecular-Genetic Description of Symptoms in Children with Autoimmune Polyglandular Syndrome Type 1: Description of a Case Series - Olga I. Krasnoperova; Elena N. Smirnova; Galina V. Chistousova (Вопросы современной педиатрии)
Clinical polymorphism of autoimmune polyglandular syndrome type 1, the presence of atypical forms and a long latent period of the target organ disease determine the difficulties in diagnosing this disease, which leads to late detection of life-threatening conditions and inadequate treatment of such patients. The article presents the results from a retrospective analysis of 7 clinical cases of autoimmune polyglandular syndrome type 1 in children hospitalized between 2006 and 2016. The clinical manifestations of the syndrome included chronic candidiasis (7 patients), hypoparathyroidism (6), chronic adrenal insufficiency (3), and autoimmune hepatitis (3). The atypical clinical signs of the disease (annular erythema, hypoplasia of tooth enamel, sialadenitis) were revealed. All children had high ( 6 norms) antibody titers to interferon , 4 — antibodies to interferon 2. In all cases of chronic adrenal insufficiency and autoimmune hepatitis, the corresponding antibodies were determined in high ( 2 norms) titers. Clinical polymorphism, prolonged monosymptomatic course, prolonged latent period between the debuts of the syndrome manifestations require modern immunological methods of diagnostics and monitoring of the residual function of the target organ for the timely initiation of therapy and prevention of crisis states.